Outcomes of untreated frequent premature ventricular complexes with normal left ventricular function. Issue 18 (29th May 2019) - Lee, Andrea K Y; Andrade, Jason; Hawkins, Nathaniel M; Alexander, George; Bennett, Matthew T; Chakrabarti, Shanta; Laksman, Zachary W; Krahn, Andrew; Yeung-Lai-Wah, John A; Deyell, Marc William
Abstract : Objective: The natural history of frequent premature ventricular complexes (PVCs) in association with preserved left ventricular ejection fraction (LVEF) is uncertain. The optimal management of this population is thus undefined. We studied the outcomes of untreated patients with frequent PVCs and preserved LVEF. Methods: This cohort study prospectively evaluated consecutive patients from 2012 to 2017, with asymptomatic or minimally symptomatic frequent idiopathic PVCs (≥5% PVCs in 24 hours; normal LVEF; no cause identified on comprehensive evaluation). No suppressive therapy (ablation or antiarrhythmic drugs) were used and patients were followed with serial ambulatory ECG monitoring and echocardiography. The primary arrhythmic outcome was reduction in PVC burden to <1% on serial ambulatory monitoring. The primary echocardiographic outcome was a reduction of LVEF to <50%. Results: One hundred patients met inclusion criteria (mean age 51.8 years, 57% female) with a median PVC burden of 18.4%. Reduction to <1% PVCs occurred in 44 of 100 patients (44.0%) at a median of 15.4 months (range 2.6 to 64.3). Recurrence was uncommon (4/44, 9.1%). Four patients (4.3%) with a persistently elevated PVC burden developed left ventricular dysfunction (LVEF <50%) during the follow-up period at a range of 53–71 months. The initial PVC burden did not predict subsequent resolution (HR 1.00(0.97, 1.03); p=0.86). Conclusions: A strategy of active surveillance is appropriate for the majority of patients with frequent idiopathic PVCs in association with preserved LVEF, owing to the low risk of developing left ventricular systolic dysfunction and the high rate of spontaneous resolution.